Projected Improvements in Accelerated Partial Breast Irradiation Using a Novel Breast Stereotactic Radiotherapy Device: A Dosimetric Analysis. (December 2017) - Snider, James W.; Mutaf, Yildirim; Nichols, Elizabeth; Hall, Andrea; Vadnais, Patrick; Regine, William F.; Feigenberg, Steven J.
Accelerated partial breast irradiation has caused higher than expected rates of poor cosmesis. At our institution, a novel breast stereotactic radiotherapy device has demonstrated dosimetric distributions similar to those in brachytherapy. This study analyzed comparative dose distributions achieved with the device and intensity-modulated radiation therapy accelerated partial breast irradiation. Nine patients underwent computed tomography simulation in the prone position using device-specific immobilization on an institutional review board–approved protocol. Accelerated partial breast irradiation target volumes (planning target volume_10mm) were created per the National Surgical Adjuvant Breast and Bowel Project B-39 protocol. Additional breast stereotactic radiotherapy volumes using smaller margins (planning target volume_3mm) were created based on improved immobilization. Intensity-modulated radiation therapy and breast stereotactic radiotherapy accelerated partial breast irradiation plans were separately generated for appropriate volumes. Plans were evaluated based on established dosimetric surrogates of poor cosmetic outcomes. Wilcoxon rank sum tests were utilized to contrast volumes of critical structures receiving a percentage of total dose ( Vx ). The breast stereotactic radiotherapy device consistently reduced dose to all normal structures with equivalent target coverage. The ipsilateral breast V 20-100 was significantly reduced ( P < .05) using planning target volume_10mm, with substantial further reductions when targeting planning target volume_3mm. Doses to the chest wall, ipsilateral lung, and breast skin were also significantly lessened. The breast stereotactic radiotherapy device's uniform dosimetric improvements over intensity-modulated accelerated partial breast irradiation in this series indicate a potential to improve outcomes. Clinical trials investigating this benefit have begun accrual.